Joining Networks in the World of Open Science - Maijala, Riitta (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
Whereas the first digital revolution of science by digitisation changed the scientific practices of data collection, analysis and reporting of results, the second digital revolution, i.e. open science, will also challenge the current roles of researchers, research organisations, libraries and publishers. From the early days of development, research libraries have joined different networks and been among the most active stakeholders working towards open science. Cohesive networks are needed for coordinated actions and support, whereas bridging networks can provide new approaches and novel information. The Finnish Open Science and Research Initiative is presented in this paper as an example of joining networks, motivating individuals and organisations to deliver high-quality services, infrastructures and competence building to promote a transition towards open science. This paper also presents milestones such as the publication of the academic publishing costs of Finnish research organisations and the maturity level of open science operating cultures in HEIs. Based on the experience of the Finnish open science initiative, joining different networks at the national level on an open mode of operation can significantly speed up the transition towards the era of open science.